2014
DOI: 10.1111/avj.12237
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism associated with acromegaly and insulin‐resistant diabetes mellitus in aSamoyed

Abstract: To the authors' knowledge, this is the first reported case that suggests that GH alterations may have clinical significance in naturally occurring hypothyroidism. Among other factors, hypothyroidism-induced GH excess should be considered as a possible cause of IR in patients suffering from hypothyroidism and concurrent DM. In such cases, DM may reverse with treatment of hypothyroidism, as was documented in this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Primary hypothyroidism in dogs is associated with increased release of GH and IGF-1 concentrations, most likely due to transdifferentiation of TSH-producing cells to cells producing cTSH and GH. 1,13,16 As T4 and cTSH were normal, hypothyroidism was considered unlikely in our dog. It was decided to pursue workup for acromegaly as a next step and perform any further evaluation for hypothyroidism (free T4 by dialysis, T4 autoantibodies) only if the respective test results would come back normal.…”
Section: Discussionmentioning
confidence: 84%
“…Primary hypothyroidism in dogs is associated with increased release of GH and IGF-1 concentrations, most likely due to transdifferentiation of TSH-producing cells to cells producing cTSH and GH. 1,13,16 As T4 and cTSH were normal, hypothyroidism was considered unlikely in our dog. It was decided to pursue workup for acromegaly as a next step and perform any further evaluation for hypothyroidism (free T4 by dialysis, T4 autoantibodies) only if the respective test results would come back normal.…”
Section: Discussionmentioning
confidence: 84%
“…The etiology of IR in HO is poorly understood and likely multifactorial. Some animal studies showed the excess secretion of growth hormone may contribute to IR in some hypothyroid dogs, but this has not yet been documented in clinical cases [ 29 ]. Our study points to plasma Hcy levels as one potential factor that may contribute to IR.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of acromegalic features [ 78 ] in intact bitches should represent a stronger recommendation for spaying since the acromegalic phenotype can be considered a biomarker of the GH influence [ 178 ] ( Figure 7 ). However, it is important to note that the acromegaly phenotype in dogs may rarely occur due to pituitary somatotrophs [ 179 , 180 ] or due to primary hypothyroidism [ 181 , 182 , 183 ]. Despite P4-controlled GH’s negative influence on insulin sensitivity being documented only during diestrus, continued intermittent GH exposure over the next estrus cycles can predict increased cumulative risk for DM, especially due to aging effects on beta-cell function [ 10 ].…”
Section: How To Best Manage Progesterone-related Diabetes Mellitus?mentioning
confidence: 99%